Genomic variability of lipooligosaccharide biosynthesis locus and sequence type among Campylobacter jejuni isolated from patients with Guillain-Barré syndrome - Md. Abu Jaher Nayeem; Shoma Hayat; Asaduzzaman Asad; Md. Golam Mostafa; Shah Nayeem Faruque; Ruma Begum; Mosabbir Ahmed; Yearul Kabir; Israt Jahan; Zhahirul Islam (Microbiology Spectrum)
ABSTRACT Lipooligosaccharide (LOS) is a crucial component of the Campylobacter jejuni (C. jejuni) cell membrane that mimics human gangliosides and can induce autoimmune neuropathies like Guillain-Barré syndrome (GBS). Approximately one in 1,000 C. jejuni infections leads to GBS, with LOS variations influencing immune response and disease induction. We aimed to investigate the sequence type and genomic variation of the LOS region of C. jejuni strains isolated from patients with GBS and enteritis. We isolated 38 GBS- and 24 enteritis-associated C. jejuni strains from Bangladesh, sequenced them on the Illumina platform, and compared their LOS regions using various bioinformatic approaches. Comparative genomic analysis between GBS-associated and enteritis-associated strains revealed that LOS classes A, B, and C were prevalent (P = 0.0001) in GBS-associated C. jejuni strains. Sequence types ST-43 and ST-2042 and clonal complexes ST-403 cc and ST-21 cc were overrepresented in GBS compared to enteritis-associated strains. All GBS-associated strains carrying LOS class C belonged to clonal complex ST-21 cc. Nucleotide variation within the LOS region differs significantly (P = 0.005) among GBS-associated and enteritis-associated strains. In GBS strains, phase variation (PV) within the LOS region was significantly higher (P = 0.004). In conclusion, the predominance of GBS-associated LOS classes, characterized by class-specific nucleotide changes and elevated phase variation, may play a critical role in the pathogenesis of GBS. However, further research on integrating DNA epigenetic analysis and metabolic profiling is needed to establish the C. jejuni-specific risk factors of GBS.IMPORTANCEThe lipooligosaccharide (LOS) biosynthesis region is the most variable and virulent genomic region of Campylobacter jejuni. This study addressed the critical gap in understanding the genomic features contributing to GBS by analyzing the LOS region of C. jejuni strains from GBS and enteritis patients. Our analysis of C. jejuni isolates from GBS and enteritis cases revealed genomic variations in the sequence type and LOS region, including distinct LOS classes (A, B, and C), higher prevalence of the cst-II gene, and significant presence of phase variability among GBS-associated C. jejuni strains. The findings highlight the association of C. jejuni LOS region in the pathogenesis of GBS. In addition, the results of this study will facilitate future comparisons by identifying genomic differences in lipooligosaccharide biosynthesis and sequence types between C. jejuni strains linked to GBS. This will enhance our understanding of the genomic variation of the LOS region and their role in GBS development.